De novo truncating NOVA2 variants affect alternative splicing and lead to heterogeneous neurodevelopmental phenotypes. Issue 9 (8th June 2022) - Scala, Marcello; Drouot, Nathalie; MacLennan, Suzanna C.; Wessels, Marja W.; Krygier, Magdalena; Pavinato, Lisa; Telegrafi, Aida; de Man, Stella A.; van Slegtenhorst, Marjon; Iacomino, Michele; Madia, Francesca; Scudieri, Paolo; et al.
Abstract: Alternative splicing (AS) is crucial for cell‐type‐specific gene transcription and plays a critical role in neuronal differentiation and synaptic plasticity. De novo frameshift variants in NOVA2, encoding a neuron‐specific key splicing factor, have been recently associated with a new neurodevelopmental disorder (NDD) with hypotonia, neurological features, and brain abnormalities. We investigated eight unrelated individuals by exome sequencing (ES) and identified seven novel pathogenic NOVA2 variants, including two with a novel localization at the KH1 and KH3 domains. In addition to a severe NDD phenotype, novel clinical features included psychomotor regression, attention deficit‐hyperactivity disorder (ADHD), dyspraxia, and urogenital and endocrinological manifestations. To test the effect of the variants on splicing regulation, we transfected HeLa cells with wildtype and mutant NOVA2 complementary DNA (cDNA). The novel variants NM_002516.4:c.754_756delCTGinsTT p.(Leu252Phefs*144) and c.1329dup p.(Lys444Glnfs*82) all negatively affected AS events. The distal p.(Lys444Glnfs*82) variant, causing a partial removal of the KH3 domain, had a milder functional effect leading to an intermediate phenotype. Our findings expand the molecular and phenotypic spectrum of NOVA2 ‐related NDD, supporting the pathogenic role of AS disruption by truncating variants and suggesting that this is a heterogeneous condition with variable clinical course. Abstract : De novo truncating NOVA2 variants lead to heterogeneous neurodevelopmental phenotypes. We identified novel clinical features (psychomotor regression, behavioral disturbances, dyspraxia, and urogenital and endocrinological manifestations), and showed that NOVA2 variants affect alternative splicing events.